Liver abscess: demographic, clinical, biochemical, imaging and microbial spectrum - Bhutto, Abdul Rabb; Abbasi, Amanullah; Rafi, Shumaila; Abro, Ali Hassan (International Journal of Research in Medical Sciences, 2019)
Background: Liver abscesses are localized suppurative destruction of liver tissue due to infections of either bacterial (Pyogenic) or protozoa (Amoebic). Historically; pyogenic liver abscess has been described since the time of hippocrates (400 BC). Despite the more aggressive approach to treatment, the mortality rate remained at 60-80%. Methods: This Cross-sectional analytical study carried out at Department of Medicine, Al-Tibri Medical College Hospital, Karachi, from June 2017 to December 2018. All participants of either gender with diagnosis of liver abscess were included in this prospective study. Patients with co morbidities like malignancy, autoimmune disease or on immunosuppressive treatment for any reason were excluded from the study. Following confirmation of the diagnosis; different characteristics of either type of liver abscess like demographic, clinical features, biochemical and imaging findings were evaluated. Results: Data of 73 subjects, 65(89.0%) males and 08(11.0%) females were analyzed with mean age was 45.42±14.518 years. Fifty-four (73.97%) patients had pyogenic liver abscess while amoebic liver abscess was found in 19(26.03%) subjects. Clinically, the most common symptom was abdominal pain, found in 66(90.4%) subjects, followed by fever in 61(83.6%), hepatomegaly in 47(64.4%), jaundice in 18(24.7%) and vomiting in 10(13.7%) cases. Demographics and clinical features are shown in (Table 1). Conclusions: Local trends have been changing and majority of liver abscess were of pyogenic liver abscesses. Clinically, clear differentiation between two types of abscesses is not possible always but few manifestations like typical symptoms, raised alkaline phosphatase and leucocytosis may be helpful.